Essentials of nursing law and ethics - Westrick, Susan J. (Jones & Bartlett Learning, 2014)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

NLN's simulation leaders give SIRC bibliography site a Makeover - Alfes, C.M.; Aronson, B.; Bethards, M.L.; Chesney, T.; De Luna, R.; Newton, R.; Weaver, A. (Nursing Education Perspectives, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: Databases; Bibliographic; Health Information Management; Humans; Internet; Models; Educational; Patient Simulation; Societies; Nursing; United States; article; bibliographic database; dept.nur; educational model; human; medical information system; nursing organization; organization and management; peer-reviewed; teaching

The knowledge patients impart - Green, C.A. (Clinical Journal of Oncology Nursing, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: Death; Humans; Knowledge; Nurse-Patient Relations; Patients; dept.nur; human; knowledge; nurse patient relationship; patient

Improving sleep-wake disturbances in patients with cancer - Lamberti, Mary Patricia (Clinical Journal of Oncology Nursing, 2014)
Patients with cancer tend to suffer sleep-wake disturbances at a higher rate than the general population. Insomnia and fatigue should be regarded as a significant patient safety issue, as poor sleep can elevate patients' risks of falls, motor vehicle accidents, and acute infectious illnesses. To alleviate those risks, oncology nurses should be familiar with effective evidence-based practices for assessing and improving patients' sleep quality.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-927-422-564-577 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Accidental Falls; Accidents; Traffic; Cancer; Humans; Infection; Interventions; Neoplasms; Patient Safety; Safety; Sleep; Sleep Wake Disorders; complication; dept.nur; falling; human; infection; neoplasm; patient safety; traffic accident